A Qualitative Investigation of Sociocultural Factors Impacting Assessment Design in Multilingual Education - Taghavian, Shima; Kheirkhah, Farshid (Assessment and Practice in Educational Sciences, 2023)
This study aimed to identify and explore the key cognitive, contextual, and emotional factors that influence how secondary school teachers interpret and use assessment data in formative assessment contexts. This qualitative study was conducted with 25 secondary school teachers from Tehran, selected through purposive sampling to ensure relevance to the research focus. Data were collected using semi-structured interviews, designed to elicit rich narratives about teachers’ experiences with interpreting various forms of assessment data. Interviews were conducted until theoretical saturation was achieved, and each session was audio-recorded and transcribed verbatim. The data were analyzed inductively using thematic analysis, supported by NVivo software. The analysis followed a multi-step coding process, beginning with open coding, followed by the identification of subthemes and overarching categories. Three core themes emerged from the data: cognitive framing of assessment data, contextual influences on data use, and emotional and relational dynamics. Teachers’ beliefs about the purpose of assessment, their level of data literacy, and prior teaching experience shaped their interpretive approaches. Institutional constraints such as time limitations, lack of infrastructure, and rigid curricula affected data use, while collaborative cultures and relevant professional development were enabling factors. Emotional responses—ranging from anxiety to motivation—also influenced interpretation, especially when connected to student-teacher relationships and ethical concerns. The study underscores that teachers’ interpretation of formative assessment data is a multifaceted process shaped not only by technical skill but also by emotional readiness, professional beliefs, and contextual conditions. Improving formative data use requires a holistic approach involving targeted professional development, collaborative environments, and structural supports.